The Influence Of Tax Justice And Tax Understanding On Tax Evavasion (Perceptions Of Students' Accounting Study Program, Faculty Of Economics, Indonesian Advent University) - Elizabeth Vania Permata; Remista Simbolon (UNIVED Press, 2024)
Study intended for evaluate impact justice as well as understanding tax on embezzlement tax according to perception student at Indonesian Adventist University, Accounting Study Program, Faculty of Economics. Respondent involved as many as 55, were obtained past method purposive sampling. Device SPSS version 22 software was used in analyze regression multiple. Acquisition studies found: (1) justice tax No influential to embezzlement tax (2) understanding tax No influential to embezzlement taxes and (3) justice taxes and understanding tax No influential to embezzlement tax